GAMBARAN HISTOPATOLOGI PANKREAS MENCIT DIABETES MELLITUS SETELAH PEMBERIAN EKSTRAK ETANOL BONGGOL BUAH NANAS (Ananas comosus (L.) Merr) - Azizah, Masayu; Ramadhanti, Fitri; Rendowati, Agnes (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
Changes in lifestyle and socio-economy in the current era of globalization can lead to increased rates of non communicable disease, one of which is diabetes mellitus (DM). This study aim   Keywords: Ananas comosus L, diabetic mice, pancreatic histopathology.